The universe. 3 : [videorecording (DVD)] : explore the edges of the unknown - Cohen, Douglas; Thompson, Erik, 1959- (A & E Television Networks : Distributed by New Video, 2007)
Famous for its striking ring formations, Saturn is perhaps the most beautiful planet in the solar system. The Milky Way is only one of the over 100 billion galaxies thought to exist, and each is composed of as many as a trillion stars. The birth of a star is a spectacular events, as gravity brings together massive molecular clouds over millions of years to create these enormous galactic furnaces. The gargantuan planets Jupiter, Saturn, Uranus, and Neptune circle the edge of the Solar System.